從教育社會學視角探察Hilda Taba社會科 課程發展理論 Exploring Hilda Taba’s Social Studies Curriculum Development Theory from the Perspectives of Sociology of Education - 鍾鴻銘 Horng-Ming Jong (臺灣教育社會學研究, 2023)
本研究旨在從教育社會學的角度探察Taba社會科課程發展理論的貢獻與 啟示。Taba的社會科課程理論乃歷經三次重要教育史事件淬鍊而得：八年研究、群際教育與加州康特拉科斯塔郡社會科課程改革方案。參與八年研究時，Taba負責評鑑學生的社會感受性。有了相關工作經驗後，Taba受邀主持與社會感受性相關的群際教育計畫。其後Taba進一步受邀主持加州康特拉科斯塔郡社會科課程改革方案。Taba將畢生積累的社會科教育理念盡瘁於康特拉科斯塔郡社會科課程改革方案之中。本研究的發現，從教育社會學的角度觀之，諸如：民主的公民資質培育應是教育的核心宗旨；關注學生對多元文化社會議題的社會感受性；從教師知識控制走向學生知識建構的課堂社會。 This article explores Taba’s social studies curriculum development theory and its contributions and implications. Taba’s social studies curriculum development theory was refined through three important events in the history of education: the Eight-Year Study, intergroup education, and the Contra Costa County Social Studies Curriculum Project. In the Eight-Year Study Taba was responsible for evaluating students’ social sensibility. Based on the Eight-Year Study work experiences, Taba was invited to host intergroup education programs related to social sensibility. After intergroup education program ended, Taba was then invited to preside over the social studies curriculum reform project in Contra Costa County, California. Taba embodied the social studies educational ideas accumulated throughout his life in Contra Costa County social studies curriculum project. From the perspectives of educational sociology, Taba’s social studies curriculum development theory has implications worthy of our consideration: the cultivation of democratic citizenship should be the aim of our education; student social sensitivity to multicultural issues should receive attention; and the social atmosphere of classroom should move from teachers’ knowledge control to students’ active knowledge construction.